Exome sequencing analysis identifies frequent oligogenic involvement and FLNB variants in adolescent idiopathic scoliosis. Issue 6 (7th May 2020) - Jiang, Heng; Liang, Shulun; He, Kai; Hu, Jinghua; Xu, Enjie; Lin, Tao; Meng, Yichen; Zhao, Jianquan; Ma, Jun; Gao, Rui; Wang, Ce; Yang, Fu; et al.
Abstract : Background: Adolescent idiopathic scoliosis (AIS) is a genetically heterogeneous disease characterised by three-dimensional deformity of the spine in the absence of a congenital spinal anomaly or neurological musculoskeletal disorder. The clinical variability and incomplete penetrance of some genes linked with AIS indicate that this disease constitutes an oligogenic trait. Objective: We aimed to explore the oligogenic nature of this disease and identify novel AIS genes. Methods: We analysed rare damaging variants within AIS-associated genes by using exome sequencing in 40 AIS trios and 183 sporadic patients. Results: Multiple variants within AIS-associated genes were identified in eight AIS trios, and five individuals harboured rare damaging variants in the FLNB gene. The patients showed more frequent oligogenicity than the controls. In the gene-based burden test, the top signal resided in FLNB . In functional studies, we found that the AIS-associated FLNB variants altered the protein's conformation and subcellular localisation and its interaction with other proteins (TTC26 and OFD1) involved in AIS. The most compelling evidence of an oligogenic basis was that the number of rare damaging variants was recognised as an independent prognostic factor for curve progression in Cox regression analysis. Conclusion: Our data indicate that AIS is an oligogenic disease and identify FLNB as a susceptibility gene for AIS.